On Some Noncoercive Variational Inequalities - Gallo, А.; Piccirillo, A. M.; Toscano, L. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We study existence and regularity of solutions of noncoercive variational inequalities.